The Influence of Corporate Social Responsibility on Company Value with Corporate Governance as a Moderator Variable - Tithon Anggara Eka Permana (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2020)
Corporate Social Responsibility (CSR) is being carried out intensively in Indonesia to prove that companies care about their surrounding environment. This study examined the effect of CSR on company value by using Corporate Governance (CG) as a moderating variable. This study aimed to determine the effect of CSR on company value in the manufacturing sector by using CG as a moderator. This is a quantitative research, with sample as many as 112 manufacturing companies listed on the IDX during 2013-2015. This study proved that CSR affects corporate value. In contrast, CG as a moderator does not affect the relationship between CSR and company value.Keywords: Corporate Social Responsibility, Institutional Ownership, Tobin's Q